DC-DC Chopper Excitation Control of WRSG for MPPT in Offshore Wind Farm. (2015) - Pisharody, Sreenidhi; Vanitha, V.
Abstract: This paper gives an idea of different state of the art of offshore wind farm configurations. One of the configurations uses Wound Rotor Synchronous Generator (WRSG), which is connected to HVDC grid through diode bridge rectifier. Field excitation of the generator is controlled for achieving Maximum Power Point Tracking (MPPT) to have full utilization of wind power. The most important feature of the suggested prototype is its low cost and high efficiency. A working model of this configuration is implemented in hardware using DSPIC and the results are verified.